Effects of early communication intervention on speech and communication skills of preterm infants in the neonatal intensive care unit (NICU): A systematic review. Issue 4 (August 2019) - Harding, C.; Levin, A.; Crossley, S.-L.; Murphy, R.; van den Engel–Hoek, L.
Abstract: Having a preterm infant is challenging for parents and families, with increased risk of psychological stress. Being separated from an infant, and dealing with the disruption to family life can impact on the development of parent – infant interaction and early bonding. These early interactive experiences are important in the development of communication skills. The antecedents for receptive and expressive language development can be supported and shaped in the neonatal unit. As preterm infants are at risk of speech, language and communication difficulties, providing parents with information about language development and strategies to promote communication are essential to integrate into neonatal care. This systematic review identified only five papers which investigated parent – infant interaction and the specific attributes associated with providing a good communication environment on the NICU. Due to the small number and differing outcome measures, a full meta –analysis was not possible. The authors recommend a clearer distinction between language and communication literature alongside investigations which have studied bonding and improving mental health for carers post pre-term birth.